Falls Among Community-Dwelling Older Adults in Jamaica. (20th December 2014) - Mitchell-Fearon, Kathryn; James, Kenneth; Waldron, Norman; Holder-Nevins, Desmalee; Willie-Tyndale, Douladel; Laws, Hazel; Eldemire-Shearer, Denise
The objective of this study is to estimate the prevalence of and risk factors for falling among community-dwelling older adults in Jamaica. A two-stage cluster sample design was used to recruit a nationally representative sample of 2, 943 older adults. The fall prevalence in the past 6 months was 21.7%. In univariate analysis, a significantly greater proportion of women, the increasingly old, rural residents, persons with vision problems (including cataracts), and those with key chronic conditions reported falling in this period compared with those without these respective attributes ( p < .05). The majority of falls reported have occurred in the home (54.3%), and restriction of activities due to fear of falling was reported by 34.6% of respondents. Logistic regression found sex, area of residence, eyesight problems, cataracts, high blood pressure, and depression to be independent risk factors for falling. The falls in older adults represent a major public health issue. Identification of modifiable risk factors in developing countries such as Jamaica may help in the development of appropriate strategies to reduce fall risk.